Parents' perception on the effects of inclusion on the socio-emotional competencies of regular children and children with special needs - Yu, Hui-Yu (Animo Repository, 2005)
This descriptive survey sought to determine the parents perceptions on the effects of inclusion on the socio - emotional competencies of regular children and children with special needs. It specifically aimed to determine whether there is a significant difference between the perception of parents on the effects of inclusion on the socio - emotional competencies of regular children and children with special needs. The study involved 34 parents of regular students and another 34 parents of children with special needs in an inclusive classroom setting in three different public schools in Pasay City and four in Manila. There were 9 male and 25 female regular students while there were 16 male and 18 female children with special needs. There were 21 students with impaired hearing and five gifted. The findings revealed that the perception of parents of children with special needs on the effects of inclusion on their children's socio-emotional competencies varied from those of the parents of regular children. It was found out that there was a significant difference between the perception of regular and special parents on their children socio-emotional competencies.